Cancer Incidence in Asbestos-Exposed Workers: An Update on Four Finnish Cohorts - Pia Nynäs; Eero Pukkala; Harri Vainio; Panu Oksa (Elsevier, 2017)
Background: We assessed the cancer risks of four different Finnish asbestos-exposed cohorts. We also explored if the cohorts with varying profiles of asbestos exposure exhibited varying relative risks of cancer. Methods: The incident cancer cases for the asbestos-exposed worker cohorts were updated to the end of 2012 using the files of the Finnish Cancer Registry. The previously formed cohorts consisted of asbestos mine workers, asbestosis patients, asbestos sprayers, and workers who had taken part in a screening study based on asbestos exposure at work. Results: The standardized incidence ratio (SIR) for mesothelioma varied from about threefold to > 100-fold in the different cohorts. In the screening cohort the SIR for mesothelioma was highest in 2003-2007, In other cohorts it was more constant in 5-year period inspection. The SIR for lung cancer was about twofold to tenfold in all except the screening cohort. Asbestos sprayers were at the highest risk of mesothelioma and lung cancer. Conclusion: The SIR for mesothelioma is high in all of the cohorts that represent different kinds of asbestos exposure. The smaller SIR for mesothelioma in the screening cohort with lowest level of asbestos exposure might suggest dose-responsiveness between asbestos exposure and mesothelioma. It does seem that the highest risk of lung cancer in these cohorts except in the youngest of the cohorts, the screening cohort, is over. The highest SIR for lung cancer of the asbestosis patient and sprayers cohort is explained by their heavy asbestos exposure.